2018
DOI: 10.1021/acs.macromol.8b01707
|View full text |Cite
|
Sign up to set email alerts
|

Syndioselective Polymerization of a BN Aromatic Vinyl Monomer

Abstract: A new synthetic platform accessing stereoregular polar polyolefins is introduced. We showcase the stability of aromatic azaborine derivatives by demonstrating the syndioselective polymerization of BN 2-vinylnaphthalene (BN2VN) by a monocyclopentadienyl titanium complex. Homogeneous early transition metal catalysts are well-established systems for the synthesis of highly stereoregular syndiotactic polystyrene (sPS), but the oxophilic nature of these complexes results in catalyst decomposition with polar monomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Initial efforts focused on Lewis acid catalysts, given the observed stability of BN2VN to Lewis acidic coactivators in coordination polymerization. 16,17 However, a screen of several Al- and B-based Lewis acids known to promote styrene cationic polymerization failed to initiate BN2VN polymerization (Table 1). In contrast to styrene polymerizations conducted as control reactions, only unreacted starting material was observed by 1 H NMR spectroscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial efforts focused on Lewis acid catalysts, given the observed stability of BN2VN to Lewis acidic coactivators in coordination polymerization. 16,17 However, a screen of several Al- and B-based Lewis acids known to promote styrene cationic polymerization failed to initiate BN2VN polymerization (Table 1). In contrast to styrene polymerizations conducted as control reactions, only unreacted starting material was observed by 1 H NMR spectroscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…15 We also reported the first example of polymerization of a BN aromatic monomer by a non-radical mechanism; we observed highly syndioselective coordination–insertion polymerization by the action of the cationic complex arising from Cp*TiMe 3 /B(C 6 F 5 ) 3 . 16 Later work by Cui et al found that Sc-complexes were also effective for syndioselective polymerization of BN2VN. 17 The stability of BN2VN to coordination polymerization is notable, given the use of highly Lewis acidic complexes such as B(C 6 F 5 ) 3 or methylalumoxane (MAO), and suggested the potential viability of cationic polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant polymers are defined by 1 H and 13 C NMR spectrum analyses and assigned according to the literature. [ 24 ] The methine(H1) and methylene protons(H2) of the polymer obtained from 4 show as broad resonances like atactic poly(BN2VN) ( Figure ). Whilst poly(BN2VN) isolated from 5 gives much sharper peaks with distinct splitting, correspondingly, methine carbon C1 provides much sharper resonance as compared with that from 4 ( Figure ), suggesting that 5 is more highly stereoselective than 4 .…”
Section: Figurementioning
confidence: 99%
“…No obvious resonance of mm triads is observed and thus the syndiotacticity value of rr = 90% was calculated according to the integral value of the rr triads, to our knowledge, which is the highest value. [ 7,24 ]…”
Section: Figurementioning
confidence: 99%
“…A possible strategy to overcome the inherent differences in the reactivity of two monomers in radical copolymerization is to exploit a post-polymerization modification reaction that is specific for one type of monomer unit. [13][14][15][16][17][18][19] In this manner, copolymerization of two monomers with similar polymerizability can lead to polymeric precursors for copolymers with compositions and microstructures that are inaccessible by direct copolymerization. Indeed, post-polymerization methods [20][21][22][23][24] to produce polymers and copolymers containing olefins have been recently reported via either deoxygenation of poly(methyl acrylate) 25 or post-functionalization and subsequent grafting-from polymerization from polyethylene or polypropylene.…”
Section: Introductionmentioning
confidence: 99%